Penggunaan Metode ABC Analysis dalam Pengelolaan Barang Bekas untuk Perancangan Layout Gudang di UD. Barokah Mulia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The management of used goods in warehouses involves a high level of complexity due to the wide variety of item types, differences in economic value, and limitations in space and labor. These conditions result in unstructured item arrangement, difficulties in determining item priorities, and inefficient loading processes caused by relatively long material handling distances. This study aims to analyze the application of the ABC Analysis method to improve layout efficiency and the management of used goods at the warehouse of UD. Barokah Mulia Rongsok. The research method employed is descriptive quantitative with a case study approach. Data were collected through observation, interviews, and warehouse record documentation, then analyzed using the ABC Analysis method as well as an analysis of the relationship between material handling distance and loading time. The results show that Category A items have the highest contribution in terms of value and movement frequency; however, under existing conditions, these items are still located far from the loading area. In addition, a relationship was found between material handling distance and loading duration. Based on these findings, a proposed warehouse layout was developed that prioritizes placing Category A items closer to the loading door, thereby potentially improving warehouse layout efficiency.